Potential ability of phytochemical in inhibition of invadopodia formation and HIF-1α in cancer metastasis - Hamad, Hamad Ali; Gopalsamy, Banulata; Cheah, Yoke Kqueen; Md Hashim, Nur Fariesha (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Cancer metastasis is a multistep process, which results in cancer cells disseminating to other organs. The crucial metastasis step involves cancer invasion which occurs via actin-protrusion by invasive malignant cells, termed as invadopodia. In solid tumours, invadopodia formation increases as a result of hypoxia which is found to be resistant against chemotherapy and radiotherapy. Phytochemicals have been potentially identified as a prime source of effective conventional drugs for metastasis treatments, which target cancer cell invasion, particularly molecular components of the invadopodia formation. The Hypoxia-Inducible Factor-1α (HIF-1α) is an essential target in terms of treatment for hypoxic tumour, as well as helping to identify the mode of action for the drugs, particularly phytochemical compounds. The aim of this review is to highlight the current development with regards to the ability of phytochemicals in targeting cancer metastasis, as well as phytochemical compounds which are able to inhibit HIF-1α and invadopodia formation. The use of phytochemicals for targeting hypoxic cancer cells may open new prospects for reducing cancer metastasis.